Catalytic Asymmetric α-Amination of α-Branched Ketones via Enol Catalysis - Shevchenko, Grigory A.; Pupo, Gabriele; List, Benjamin (Synlett, 2015)
We report a highly enantioselective α-amination of α-branched ketones catalyzed by a chiral phosphoric acid employing azodicarboxylates as reagents. The desired products were obtained in good to excellent yields and enantioselectivities.
Keywords: asymmetric synthesis; Brønsted acid catalysis; electrophilic amination; α-branched ketones; enol catalysis; azodicarboxylates